Assessment of the Potential and Current Limitations of Integrating CFD and Structural Analyses for the Design of Offshore Wind Turbines - Kandt, Julius (My University, 2019)
While the need for electric energy grows over the years, the environmental impact is an important factor for the energy generation as well. Wind power plays a major role among the renewable energies nowadays. However, the available space onshore is restricted and complex terrain complicates the use of various areas even more. Among others this is one of the reasons why the use of offshore wind power stations becomes more attractive. Therefore, the assessment of offshore sites is an important aspect that may decide whether to place a wind plant or not. For this Computational Fluid Dynamics have become a popular approach over the past years replacing simpler spectral methods. In this study the modeling of the Atmospheric Boundary Layer for the generation of an offshore environment using a Large Eddy Simulation was investigated. Overall it was found, that this method is able to reproduce the Atmospheric Boundary Layer well, especially when it comes to the mean velocity field. Nevertheless, inaccuracies were found considering the Reynolds stresses, especially the shear components. Moreover, the flow field obtained with the Large Eddy Simulation was compared to a spectral flow field and the dynamic response of two wind turbines was assessed using the aero-elastic solver FAST. The results of both methods are in close agreement to each other. Therefore, the integration of the aero-elastic solver FAST into the process of an analysis using Computational Fluid Dynamics works well. Finally, the performance of the Actuator Disk and Actuator Line model was tested in Star-CCM+. The effect of these models on the flow field was investigated as well as the thrust and torque calculation. It was found that both models do not match the FAST results very well in terms of the torque prediction. However, the thrust calculation of the Actuator Line Model comes close to the results from FAST. Several aspects were outlined for further investigation.
Keywords: Energi; Hållbar utveckling; Maskinteknik; Strömningsmekanik och akustik; Energy; Sustainable Development; Mechanical Engineering; Fluid Mechanics and Acoustics